Avaliação de dietas contendo silagem de maniçoba (manihot pseudoglaziovii pax. et. k. hoffman) para terminação de caprinos no semi-árido brasileiro - Medina, Fernando Thomaz (2005)
The present work aimed to evaluate the consumption, the digestibility of nutrients, the daily average weight gain, the nutriment conversion, as well as the weight and yield of carcass of goats being held in confinement during the final stage, receiving diets containing silage of manioc associated to different energy sources. 15 goats without defined racial standard, not castrated, with initial average life weight of 21,0 kg, were allocated in delineation in casual blocks, with three treatments and five repetitions. To determine the consumption and the coefficient of apparent digestibility of nutrients in the diets, a digestibility test was undertaken that consisted of 14 days of adaptation and five total excrement collections, being the diets composed by 54% bulky silage of manioc (Manihot pseudoglaziovii Pax. Et. K. Hoffman) and 46% concentrated energetic food: corn meal (Zea mays), scraped cassava (Manihot esculenta Crantz), enriched with 1.8% urea, and cactus forage meal (Opuntia ficus indica), enriched with 1.1% urea. A confinement period of 63 days was used to determine the daily average weight gain, nutriment conversion, and weight and yield of carcass. During this phase of the experiment, the combination of silage and scraped cassava was excluded, in function of the intoxication possibility for acid cianidrico, potentates by the combination; detected in the digestibilidade period and the statistic delineation consisted of two treatments and eight repetitions. Higher consumption of DM, OM,4 TC, EE and TDN was observed regarding the diets composed by silage and corn meal, as well as silage and cactus forage meal, presenting the latter also higher (P<0.05) consumption of NDF, ADF and CP. The type of energy source of the diet influenced the apparent digestibility coefficient of DM, OM, EE and TC, with higher values for the combination of silage and corn meal, in comparison to scraped cassava and cactus forage meal, which did not differ between each other (P>0.05). The apparent digestibility coefficient of CP, NDF and ADF was influenced by the energy source associated to the silage. As to the daily average weight gain, differences (P<0.05) were verified between the diets, with higher gains for the combination of silage and corn meal. The nutriment conversion of dry material, loss from cooling, and real performance was not influenced (P>0.05) by the energy source. There were differences (P<0.05) for weight at, yield of carcass (hot and cold), for loss from cooling and real performance among the diets. The Life weight at slaughter, weight and yield of carcass (hot and cold), were higher (P<0.05) for the diet composed by silage and corn meal. The relationship silage manioc (54%): concentrated scraped cassava 46%), it can cause intoxication problems, potency of production of acid cianidrico. Energetic sources corn meal and cactus forage meal, to be capable to nutritious in enough amount to guarantee medium of up to 80g/dia, when combined with silage manioc, in diets for goats.